In situ cell cycle analysis in giant cell tumor of bone reveals patients with elevated risk of reduced progression-free survival - Maros, Máté E.; Schnaidt, Sven; Balla, Péter; Kelemen, Zoltán; Sapi, Zoltan; Szendroi, Miklos; Laszlo, Tamas; Forsyth, Ramses; Picci, Piero; Krenacs, Tibor (Bone, 2019)
Objective - Giant cell tumor of bone (GCTB) is a frequently recurring locally aggressive osteolytic lesion, where pathological osteoclastogenesis and bone destruction are driven by neoplastic stromal cells. Here, we studied if cell cycle fractions within the mononuclear cell compartment of GCTB can predict its progression-free survival (PFS). - Methods - 154 cases (100 primaries and 54 recurrent) from 139 patients of 40 progression events, was studied using tissue microarrays. Ploidy and in situ cell cycle progression related proteins including Ki67 and those linked with replication licensing (mcm2), G1-phase (cyclin D1, Cdk4), and S-G2-M-phase (cyclin A; Cdk2) fractions; cell cycle control (p21waf1) and repression (geminin), were tested. The Prentice-Williams-Peterson (PWP) gap-time models with the Akaike information criterion (AIC) were used for PFS analysis. - Results - Cluster analysis showed good correlation between functionally related marker positive cell fractions indicating no major cell cycle arrested cell populations in GCTB. Increasing hazard of progression was statistically associated with the elevated post-G1/S-phase cell fractions. Univariate analysis revealed significant negative association of poly-/aneuploidy (p<0.0001), and elevated cyclin A (p<0.001), geminin (p=0.015), mcm2 (p=0.016), cyclin D1 (p=0.022) and Ki67 (B56: p=0.0543; and Mib1: p=0.0564 -strong trend) positive cell fractions with PFS. The highest-ranked multivariate interaction model (AIC=269.5) also included ploidy (HR 5.68, 95%CI: 2.62-12.31, p<0.0001), mcm2 (p=0.609), cyclin D1 (HR 1.89, 95%CI: 0.88-4.09, p=0.105) and cyclin A (p<0.0001). The first and second best prognostic models without interaction (AIC=271.6) and the sensitivity analysis (AIC=265.7) further confirmed the prognostic relevance of combining these markers. - Conclusion - Ploidy and elevated replication licensing (mcm2), G1-phase (cyclin D1) and post-G1 phase (cyclin A) marker positive cell fractions, indicating enhanced cell cycle progression, can assist in identifying GCTB patients with increased risk for a reduced PFS.